Clinical considerations of the glandular branch of the lacrimal artery. Issue 7 (23rd February 2015) - Kluckman, Matthew; Fan, Jerry; Balsiger, Heather; Scott, Gabriel; Gest, Thomas
Abstract : The lacrimal artery is classically described as a branch of the ophthalmic artery supplied by the internal carotid. In this study, 25 orbits were dissected to identify variations in glandular branching and to compare them to previously published accounts. The glandular branching patterns of the lacrimal artery fall into two categories, those that branch (56%) and those that do not branch (44%). We found the medial and lateral glandular branches to be equal in diameter with a divergence of 2.67–40.58 mm proximal to the gland parenchyma. The long glandular branches run alongside the superolateral aspect of the orbit. The lateral branch runs lateral to the lateral rectus muscle. The medial branch runs superomedial to the lateral rectus muscle and lateral to the superior rectus muscle. In relation to the lacrimal gland, the medial branch enters the superior aspect of the gland parenchyma and the lateral branch enters its inferior aspect. The average branch lengths were 17.88 mm (medial) and 13.51 mm (lateral) as measured with a Mitutoyo Absolute 1/100 mm caliper. We could not confirm the existence of a third branch supplying the lacrimal gland, as posited by other authors. The key finding in this study is that the lacrimal gland is predominantly supplied by two significant arterial branches, both of which must be identified during procedures involving the lateral orbit. Clin. Anat. 28:844–847, 2015. © 2015 Wiley Periodicals, Inc.